2022
DOI: 10.1111/cgf.14523
|View full text |Cite
|
Sign up to set email alerts
|

Seeing Through Sounds: Mapping Auditory Dimensions to Data and Charts for People with Visual Impairments

Abstract: Sonification can be an effective medium for people with visual impairments to understand data in visualizations. However, there are no universal design principles that apply to various charts that encode different data types. Towards generalizable principles, we conducted an exploratory experiment to assess how different auditory channels (e.g., pitch, volume) impact the data and visualization perception among people with visual impairments. In our experiment, participants evaluated the intuitiveness and accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 61 publications
0
6
0
1
Order By: Relevance
“…For instance, Hoque et al [25] used natural sound (e.g., bird sound) to support enhanced distinction between categorical values. Wang et al [56] show that BVI readers find certain audio channels to be more intuitive given visual encodings (e.g., pitch for bar heights) and given data type (e.g., quantitative, ordinal). In their experiment, participants indicated a need for an overview of auditory scales [56].…”
Section: Data Sonificationmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Hoque et al [25] used natural sound (e.g., bird sound) to support enhanced distinction between categorical values. Wang et al [56] show that BVI readers find certain audio channels to be more intuitive given visual encodings (e.g., pitch for bar heights) and given data type (e.g., quantitative, ordinal). In their experiment, participants indicated a need for an overview of auditory scales [56].…”
Section: Data Sonificationmentioning
confidence: 99%
“…Wang et al [56] show that BVI readers find certain audio channels to be more intuitive given visual encodings (e.g., pitch for bar heights) and given data type (e.g., quantitative, ordinal). In their experiment, participants indicated a need for an overview of auditory scales [56]. Thus, a sonification grammar should be able to express such aspects of an audio graph design definition.…”
Section: Data Sonificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Existen decenas de estudios que afirman emplear unos u otros parámetros para hacer mapeos de datos (Wang et al, 2022). A pesar de ello, aún no se ha llegado a un consenso que permita formalizar equivalencias concretas, y muchos de los autores mencionados señalan que es preciso realizar pruebas hasta encontrar la forma más acertada de realizar este mapeo para cada caso concreto.…”
Section: Cómo Representar Datos Mediante Sonidosunclassified
“…Sio et al [74] proposed a heuristics-based approach combining sonification with textual description to generate audio data narratives from a time-series dataset and Infosonics [39] presented an unconventional method to present the audio analogue of infographics combining interactive sonifications, spoken introduction, and harmonious notes. Wang et al [81] conducted experiments to find how different auditory channels affect the perception of visualization among people with visual impairments and they reported that pitch was the most instinctive channel to understand all data types (e.g., quantitative, ordinal, and nominal). However, data sonification can lead to cognitive overload [65], and integrating such techniques in online environment is challenging [43].…”
Section: Accessible Visualizationmentioning
confidence: 99%